2010
DOI: 10.1161/strokeaha.109.571356
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke in Cancer Patients With and Without Conventional Mechanisms

Abstract: Background and Methods-To assess the precise mechanisms of stroke in cancer patients, we analyzed the data for cancer patients with acute ischemic stroke registered from 6 centers in South Korea. Clinical features, risk factors, diffusion-weighted imaging lesion patterns, and laboratory findings including D-dimer levels were compared between patients with conventional stroke mechanisms (CSMs) and cryptogenic group. Results-A total of 161 patients were included in this study: 97 (60.2%) patients in the CSM grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
242
3
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(271 citation statements)
references
References 12 publications
16
242
3
10
Order By: Relevance
“…Our results are in line with the results of the earlier and largest study so far by Kim et al 13 The significance of this study, however, was limited by the fact that it did not include a control group but compared patients with cancer with and without a conventional stroke etiology.…”
Section: November 2012supporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with the results of the earlier and largest study so far by Kim et al 13 The significance of this study, however, was limited by the fact that it did not include a control group but compared patients with cancer with and without a conventional stroke etiology.…”
Section: November 2012supporting
confidence: 92%
“…[6][7][8][9][10][11][12] The largest study including 161 patients by Kim et al in 2010 differentiated between patients with cancer+stroke with and without conventional stroke etiologies and renewed the idea of cancer-associated hypercoagulation as an important stroke etiology. 13 Significantly higher d-dimer levels as well as a significantly higher rate of multiply affected vascular territories in the group of patients without conventional stroke etiology supported the idea of cancer-associated hypercoagulation with resulting cerebral embolism. This was promoted by a higher prevalence of…”
mentioning
confidence: 85%
“…15,16 Because of the advances in cancer medicine and the steadily increasing proportion of elderly people, the number of people living with cancer is increasing. As a consequence, the proportion of patients who have cancer is expected to increase among patients with stroke, especially in those without other stroke pathogeneses.…”
Section: Evaluation Of Cryptogenic Stroke With Advanced Diagnostic Tementioning
confidence: 99%
“…15 Patients with cancer-related stroke often present with progressive neurological deficits for hours to days (or even weeks) rather than sudden catastrophic events with initial maximum deficits at onset. In many patients, multifocal thromboembolism culminates in widespread infarcts of various sizes, producing confusion, lethargy, or dementia.…”
Section: Tests For Coagulopathy and Cancer Screeningmentioning
confidence: 99%
“…An autopsy-based study found that approximately 15% of all patients with cancer experienced thromboembolic events, including ischemic stroke (IS), during their clinical course [8]. Systemic cancer is related to IS via various mechanisms [9]. Specifically, cancer-related mechanisms such as coagulopathy and tumour occlusion are a common cause of IS in patients with cancer [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%